2016
DOI: 10.1007/s12035-016-9856-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion

Abstract: Chronic brain hypoperfusion (CBH) induces the accumulation of abnormal cellular proteins, accompanied by cognitive decline, and the autophagic-lysosomal system is abnormal in dementia. Whether CBH accounts for autophagic-lysosomal neuropathology remains unknown. Here, we show that CBH significantly increased the number of autophagic vacuoles (AVs) with high LC3-II levels, but decreased SQSTM1 and cathepsin D levels in the hippocampi of rats following bilateral common carotid artery occlusion (2VO) for 2 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 60 publications
4
31
0
Order By: Relevance
“…For example, che et al found that the level of miR-27a was increased in rat under chronic brain hypoperfusion condition, which induced the accumulation of autophagosomes via regulating LAMP2 expression in neuron [28]. Overexpression of miR-23b exerted neuroprotective effects on cognitive impairments after traumatic brain injury via inhibiting neuron apoptosis and attenuating neurological deficits [29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, che et al found that the level of miR-27a was increased in rat under chronic brain hypoperfusion condition, which induced the accumulation of autophagosomes via regulating LAMP2 expression in neuron [28]. Overexpression of miR-23b exerted neuroprotective effects on cognitive impairments after traumatic brain injury via inhibiting neuron apoptosis and attenuating neurological deficits [29].…”
Section: Discussionmentioning
confidence: 99%
“…The method for preparation was similar to the previous study with minor modifications [3]. The hippocampus samples from each rat were fixed in 3% glutaraldehyde in 0.1 mol/L phosphate buffer (pH 7.4) and post-fixed with 1% osmium tetroxide in Sorensen’s phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…CBH has been demonstrated to induce autophagic-lysosomal neuropathology [3], reduced dendritic spine density [4], glial activation [5], inflammatory reactions and white matter damage [6]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In neurons, autophagy is responsible for the homeostatic pathway [6,7], and is also associated with CCH induced by two-vessel occlusion (2VO) surgery. For example, the accumulation of autophagic vacuoles and elevated microtubule-associated protein 1 light chain 3 (LC3) levels were found in the cortex of 2VO rats at 2 weeks after surgery [8]. Liu et al reported that the level of LC3 was significantly increased in both the cortex and hippocampal CA1 area of 2VO rats at 5 weeks after surgery, and GABA receptors reversed the neuronal damage by activating autophagy [9].…”
Section: Introductionmentioning
confidence: 99%